2003
DOI: 10.1354/vp.40-3-328
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Detection of Apolipoprotein A-I and B-100 in Canine Atherosclerotic Lesions

Abstract: Abstract. We attempt to determine and compare the localization of apolipoproteins (apo) apoA-I and B-100 in atherosclerotic lesions of canine aortas, coronary arteries, and the peripheral arteries, using immunohistochemical techniques. Histopathologically, atherosclerotic lesions were characterized by deposition of lipids and infiltration of lipid-laden foamy cells in the tunica intima and tunica media, sometimes forming fibrofatty plaques containing abundant sudanophilic and mineralized material. Canine apoA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
2
0
4
Order By: Relevance
“…In humans, this protein belongs to negative APP and lowered plasma levels of apoA-I is considered to be correlated to an increased risk of cardiovascular diseases and atherosclerosis. The distribution of plasma lipids and lipoproteins in dogs is quite unlike that in humans, with dogs having approximately five to six times as much HDL as LDL [34]. …”
Section: Discussionmentioning
confidence: 99%
“…In humans, this protein belongs to negative APP and lowered plasma levels of apoA-I is considered to be correlated to an increased risk of cardiovascular diseases and atherosclerosis. The distribution of plasma lipids and lipoproteins in dogs is quite unlike that in humans, with dogs having approximately five to six times as much HDL as LDL [34]. …”
Section: Discussionmentioning
confidence: 99%
“…Se describen dos casos que presentaron pigmentos en la pared de los vasos sanguíneos, reportados como pigmentos derivados de la hemoglobina (1,17,18), y un caso con presencia de material basofílico compatible con deposición de minerales, descritos como focos de mineralización (3), núcleos de mineralización incipiente (6) y nódulos calcificados (13,15).…”
Section: Discussionunclassified
“…La literatura reporta una amplia gama de lesiones que pueden ser muy similares, excepto por detalles minuciosos, lo que da lugar a múltiples nombres para cada lesión, ya sea para referirse a diferentes etapas de un proceso o a diferentes procesos de arterioesclerosis (6,13,19).…”
Section: Discussionunclassified
“…There are very few studies that refer to Apo-B and pets -according to the literature it has been shown that dogs exhibit no cholesterol ester transfer protein (CETP) activity in vitro, in contrast to humans (Bailhache et al, 2004) and both cats and dogs have hormones and adipogene factors similar with other species, being affected in a similar way through obesity (Blum et al, 2008). Apolipoproteins (Apo-A, Apo-B, Apo-E) represent the proteic component of lipoproteins (LDL, HDL, VLDL); these confer structural integrity for the central hydrophobic lipids and have a role in the transport of lipids from intestinal level to the liver and the organism's cells; HDL are the predominant lipoproteins in plasma of dogs and cats (Watson, 1996) and play an important role in recognizing the receptors for lipoproteins and the regulation of certain enzimes from the lipoprotein metabolism (Sako et al, 2001(Sako et al, , 2003. Other research was focalized towards identifying and understanding the molecular level interactions between nutrients and other bioactive substances from food and genome (Simopoulos, 1989).…”
Section: Introductionmentioning
confidence: 99%